2015
DOI: 10.1007/s13312-015-0716-9
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity among adolescents – A comparative study between government and private schools

Abstract: A differential strategic plan may be needed to prevent and control obesity among adolescent school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 6 publications
4
17
1
1
Order By: Relevance
“…Our findings agree with (Patnaik et al, 2011) who reported significantly higher prevalence of overweight/obesity among private school children aged 5 to 10 years in India. The results also agree with Jagadesan et al (2014) and Patnaik et al (2015) who both reported high overweight/obesity prevalence among children in private schools. Several studies have outlined potential reasons for these differences.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings agree with (Patnaik et al, 2011) who reported significantly higher prevalence of overweight/obesity among private school children aged 5 to 10 years in India. The results also agree with Jagadesan et al (2014) and Patnaik et al (2015) who both reported high overweight/obesity prevalence among children in private schools. Several studies have outlined potential reasons for these differences.…”
Section: Discussionsupporting
confidence: 90%
“…school going students are from a lower socioeconomic group. Similar findings were reported from Bhubaneswar and Chennai by the studies of Jagadesan et al and Patnais et al 12,13 Other major factors and behaviors responsible for overweight and obesity are unhealthy food habits and lack of physical activity. These risk behaviors among overweight and obese children were compared with nonobese children.…”
Section: Discussionsupporting
confidence: 87%
“…Manuscript received: 4 th July 2017 Reviewed: 14 th July 2017 Author Corrected: 23 rd July 2017 Accepted for Publication: 31 st July 2017 Schools 10.5%). BMI, Waist Circumference and Waist-hip ratio were significantly higher among private school students [3].…”
Section: Introductionmentioning
confidence: 78%
“…Patnaik L [3] observed that prevalence of overweight / obesity was 27.8% (private schools -45.2%, government schools -10.5%).…”
Section: Discussionmentioning
confidence: 99%